Effect of Manufacturing Strategy on the Toughness Behavior of Inconel 625 Laser Metal Deposited Parts. Issue 7 (19th March 2021) - Verdi, Davide; Varadaraju, Naresh; Tan Zhi'En, Eddie; Patran, Alin
Abstract : Nickel‐based superalloys are broadly used to produce high value added components in industrial sectors such as oil and gas, aerospace, energy production, etc. Additive manufacturing represents a viable alternative family of processes for near‐net shape fabrication. Herein, it presents results related to the toughness behavior of laser metal deposited Inconel 625 samples under impact tests, in the as‐deposited and post heat‐treated condition. Laser metal deposition is used to build Inconel 625 Charpy impact tests samples in two different orientations: vertical and horizontal. Half of the samples for each build orientation are subjected to annealing heat treatment whereas the remainder are kept as‐built. Distinct toughness behaviors are observed, with the vertical builds exhibiting a higher absorbed energy than the horizontal one. Furthermore, a decrease in absorbed energy after heat‐treatment is observed in the Charpy impact test results for both deposition orientation samples. A similar behavior is observed through Vickers microhardness measurements. However, in this case, although the horizontal deposited samples result always harder than the vertical ones, the heat treatment reduces the hardness difference between the two deposition directions. The obtained results highlight the influence of the manufacturing strategy on the toughness of the final components. Abstract : The influence of the manufacturing strategy on the toughness of laser metal deposited Inconel 625 final components is studied. Vertically and horizontally built samples are subjected to Charpy impact tests. The distribution of the secondary phases, formed during the deposition and heat treatment, with respect to the direction of the impact, affects the amount of absorbed energy.